How reliable are clinical systems in the UK NHS? A study of seven NHS organisations - Burnett, S; Franklin, B; Moorthy, K; Cooke, M; Vincent, C (2012)
Background: It is well known that many healthcare systems have poor reliability; however, the size and pervasiveness of this problem and its impact has not been systematically established in the UK. The authors studied four clinical systems: clinical information in surgical outpatient clinics, prescribing for hospital inpatients, equipment in theatres, and insertion of peripheral intravenous lines. The aim was to describe the nature, extent and variation in reliability of these four systems in a sample of UK hospitals, and to explore the reasons for poor reliability. Methods: Seven UK hospital organisations were involved; each system was studied in three of these. The authors took delivery of the systems' intended outputs to be a proxy for the reliability of the system as a whole. For example, for clinical information, 100% reliability was defined as all patients having an agreed list of clinical information available when needed during their appointment. Systems factors were explored using semi-structured interviews with key informants. Common themes across the systems were identified. Results: Overall reliability was found to be between 81% and 87% for the systems studied, with significant variation between organisations for some systems: clinical information in outpatient clinics ranged from 73% to 96%; prescribing for hospital inpatients 82-88%; equipment availability in theatres 63-88%; and availability of equipment for insertion of peripheral intravenous lines 80-88%. One in five reliability failures were associated with perceived threats to patient safety. Common factors causing poor reliability included lack of feedback, lack of standardisation, and issues such as access to information out of working hours. Conclusions: Reported reliability was low for the four systems studied, with some common factors behind each. However, this hides significant variation between organisations for some processes, suggesting that some organisations have managed to create more reliable systems. Standardisation of processes would be expected to have significant benefit.